Investigation of modified alumina for remediation of contaminated oil: a review / Muhammad Zahiruddin Ramli and Nurul Najwa Zam Bere - Ramli, Muhammad Zahiruddin; Zam Bere, Nurul Najwa (2020)
Increases in human population and industrial activity unavoidably have produced large volume of oily wastewater and increased in demand for clean water. The performance of conventional methods in wastewater treatments showing insignificant effect as its drawbacks to the environment such as large volume of sludge produced and high cost of reagents. However, adsorption by alumina have shown a promising potential to be developed as new material for wastewater treatment attributed by its modifiable surface area and high sorption capacity. Sol-gel method is highlighted as the modification route for materials’ morphology and topography due to its simplicity. In this review, data for the effect and performance of modified alumina sucrose templated via sol-gel method is collected, analyzed, compared, and predicted. Review discovered that surfactants does affect material porosity and alumina templated with sucrose demonstrated high porosity. Alumina-sucrose templated with 491 m2/g surface area, 0.62 cm3/g pore volume, and 4.20 nm pore diameter is predicted to have better removal performance with removal of >83% oil and grease, >87.83% COD, and >86.6% BOD, compared to non-modified alumina. From review, surface modification with surfactant templated is proven improve material’s morphology and performance.